WAYS AND TYPES OF STUDYING LOGOPEDIC MASSAGE - Ganiyeva Ozoda (Bright Mind Publishing, 2025)
This article is about the method of correctional and pedagogical influence of speech therapy massage, the elimination of severe speech defects, the provision of theoretical and practical knowledge, skills and qualifications for the effective correction of speech defects with the help of speech therapy massage. The physiological effect of speech therapy massage on the human body, as well as the special effect of speech therapy massage, the acquisition of practical skills of speech therapy massage, and the ability to differentially select a complex of massage movements depending on the emotional and muscular state of each child with speech pathology.
Keywords: Speech therapy massage, speech, organism, methods, stroking, kneading and tapping.